Muslim networks from Hajj to hip hop - Cooke, Miriam; Lawrence, Bruce B. (Islamic civilization & Muslim networks., 2005)
This volume selects major moments and key players from the seventh century to the twenty-first that have defined Muslim networks as the building blocks for Islamic identity and social cohesion. The essays provide a long view of Muslim networks, correcting both scholarly omission and political sloganeering.